Power transient stability enhancement - Liang, Jiayue (2018)
A micro-grid is commonly used in today’s power generation system. This report has explained why there is a rising trend of integrating renewable energy into power system and the different components that constitute a micro-grid system. It has also discussed on the challenges that micro-grid system is facing at the moment and some of the solutions proposed by researchers to tackle the respective challenges. The objective of this project is to simulate a micro-grid system with solar, wind turbine, diesel generator, energy storage system and a load. 4 different types of disturbance are added to the system to simulate a real-life scenario. Results are then mainly analyzed with regards to the power and frequency. Lastly, future work is brought up on how to improve the existing modelling of micro-grid system.